A family of rhomboid-like genes: Drosophila rhomboid-1 and roughoid/rhomboid-3 cooperate to activate EGF receptor signaling. - Wasserman, J; Urban, S; Freeman, M (2000)
As in mammals, the Drosophila EGF receptor controls many aspects of growth and development. The rate limiting component of Drosophila Egfr signaling is Rhomboid, a seven transmembrane domain protein, whose expression prefigures Egfr signaling. Little is known about the molecular mechanism of Rhomboid function but genetic evidence suggests that it controls the activation of the ligand Spitz, a TGFalpha-like factor. Spitz/Egfr signaling regulates cell determination in the eye but here there is no apparent function for Rhomboid, an observation that casts doubt on this prevailing model of Rhomboid function. We describe our identification of six new rhomboid-like genes in Drosophila, and a large family of related genes present in organisms as diverse as bacteria and mammals; a human rhomboid homolog has also recently been described. Drosophila rhomboid-3 corresponds to the roughoid mutation; it cooperates with rhomboid-1 to control Egfr signaling in the eye, thereby solving the puzzle of the apparent lack of Rhomboid-1 function there. Rhomboid-1 and Roughoid/Rhomboid-3 act in the signal-emitting not signal-receiving cell, supporting the idea that Spitz activation is regulated by Rhomboid-like molecules.